ANALISIS PEMASARAN POLA USAHATANI MINA-PADI-ITIK (PARLABEK) DI DESA KARANG KEMIRI KECAMATAN BELITANG KABUPATEN OGAN KOMERING ULU TIMUR (JASEP, 2015)
Marketing analysis pattern of rice-fish farming-duck (PARLABEK) in Karang Pecan Belitang District of East Ulu Ogan Ogan. The purpose of this study to determine how big the marketing margin and the farmer's share received by farmers. Results obtained marketing of products rice-fish-duck has a marketing margin for rice at Rp 2,500 / kg, fish Rp 12.000 / kg, ducks (meat) Rp. 15,000 / kg, ducks (egg) Rp 1,300 / kg, and marketing margin of 31.25% relative to rice, fish 40%, ducks (meat) 30%, ducks (egg) 48% and the farmer's share of each rice 68, 75, fish 60%, ducks (meat) of 70% and ducks (egg) 52% .Sedangkan marketing channels usahatai pattern of rice-fish-iti has two marketing channels that direct marketing channels to consumers and marketing channel through middlemen.